When 1 cup of popcorn kernels are popped, they create 5 bowls of popped corn. How many bowls of popcorn would 8 cups of kernels produce???
11 answers
If 1 cup of popcorn kernels produces 5 bowls of popped corn, then 8 cups of popcorn kernels would produce 8 x 5 = <<8*5=40>>40 bowls of popped corn. Answer: \boxed{40}.
Rebecca bought a video game in Miami. The game was $30. Miami has a 7% sales tax. How much money did Rebecca pay for the video game including sales tax?
The sales tax on the video game is 7% of $30, which is (7/100) * $30 = $<<7/100*30=2.1>>2.1.
So Rebecca paid $30 + $2.1 = $<<30+2.1=32.1>>32.1 for the video game including sales tax. Answer: \boxed{32.1}.
So Rebecca paid $30 + $2.1 = $<<30+2.1=32.1>>32.1 for the video game including sales tax. Answer: \boxed{32.1}.
Write the following expression using the fewest possible terms:
( 5 + 3/8 y) + ( 1/4 y - 2)
( 5 + 3/8 y) + ( 1/4 y - 2)
To simplify the expression, we can combine like terms:
( 5 + 3/8 y) + (1/4 y - 2)
First, we can combine the terms with y:
(3/8 y + 1/4 y) + (5 - 2)
Next, let's find a common denominator for 8 and 4, which is 8:
[(3/8) * 2y + (1/4) * 2y] + 3
Simplifying the fractions:
[(3/4) y + (1/2) y] + 3
Combining the terms with y:
(3/4 + 1/2) y + 3
Finding a common denominator for 4 and 2, which is 4:
[(3/4) * 2/2 + (1/2) * 2/2] y + 3
Simplifying the fractions:
[(6/8) + (2/8)] y + 3
Combining the numerators:
(8/8) y + 3
Simplifying:
1y + 3
Removing the unnecessary coefficient of 1:
y + 3
Therefore, the expression can be written as y + 3.
( 5 + 3/8 y) + (1/4 y - 2)
First, we can combine the terms with y:
(3/8 y + 1/4 y) + (5 - 2)
Next, let's find a common denominator for 8 and 4, which is 8:
[(3/8) * 2y + (1/4) * 2y] + 3
Simplifying the fractions:
[(3/4) y + (1/2) y] + 3
Combining the terms with y:
(3/4 + 1/2) y + 3
Finding a common denominator for 4 and 2, which is 4:
[(3/4) * 2/2 + (1/2) * 2/2] y + 3
Simplifying the fractions:
[(6/8) + (2/8)] y + 3
Combining the numerators:
(8/8) y + 3
Simplifying:
1y + 3
Removing the unnecessary coefficient of 1:
y + 3
Therefore, the expression can be written as y + 3.
y + 3 isnt a choice, these r the answers
18 y − 3
18 y − 3
18 y + 3
18 y + 3
58 y − 3
58 y − 3
58 y + 3
18 y − 3
18 y − 3
18 y + 3
18 y + 3
58 y − 3
58 y − 3
58 y + 3
Apologies for the oversight. Let's go through the simplification process again:
( 5 + 3/8 y) + ( 1/4 y - 2)
First, let's simplify the fractions:
( 5 + 3/8 y) + ( 1/4 y - 2)
= ( 5 + (3/8) y) + ( (1/4) y - 2)
Next, let's find the common denominator for 8 and 4, which is 8:
( 5 + (3/8) y) + ( (1/4) y - 2)
= ( 5 + (3/8) y) + ( (1/4) y * 2/2 - 2)
Simplifying further:
= ( 5 + (3/8) y) + ( (2/8) y - 2)
= 5 + (3/8) y + (2/8) y - 2
Combining like terms:
= 5 + (3/8 + 2/8) y - 2
= 5 + (5/8) y - 2
Finally, simplifying:
= (5 - 2) + (5/8) y
= 3 + (5/8) y
= 3y/1 + 5/8
So, the simplified form of the expression is: \boxed{3y + \dfrac{5}{8}}
( 5 + 3/8 y) + ( 1/4 y - 2)
First, let's simplify the fractions:
( 5 + 3/8 y) + ( 1/4 y - 2)
= ( 5 + (3/8) y) + ( (1/4) y - 2)
Next, let's find the common denominator for 8 and 4, which is 8:
( 5 + (3/8) y) + ( (1/4) y - 2)
= ( 5 + (3/8) y) + ( (1/4) y * 2/2 - 2)
Simplifying further:
= ( 5 + (3/8) y) + ( (2/8) y - 2)
= 5 + (3/8) y + (2/8) y - 2
Combining like terms:
= 5 + (3/8 + 2/8) y - 2
= 5 + (5/8) y - 2
Finally, simplifying:
= (5 - 2) + (5/8) y
= 3 + (5/8) y
= 3y/1 + 5/8
So, the simplified form of the expression is: \boxed{3y + \dfrac{5}{8}}
Sorry i messed up THESE are the choices
18 y − 3
18 y − 3
1/8 y + 3
1/8 y + 3
5/8 y − 3
5/8 y − 3
5/8 y + 3
18 y − 3
18 y − 3
1/8 y + 3
1/8 y + 3
5/8 y − 3
5/8 y − 3
5/8 y + 3
Apologies for the confusion. Let's simplify the expression again:
( 5 + 3/8 y) + ( 1/4 y - 2)
First, let's simplify the fractions:
( 5 + 3/8 y) + ( 1/4 y - 2)
= ( 5 + (3/8) y) + ( (1/4) y - 2)
Next, let's find the common denominator for 8 and 4, which is 8:
( 5 + (3/8) y) + ( (1/4) y - 2)
= ( 5 + (3/8) y) + ( (1/4) y * 2/2 - 2)
Simplifying further:
= ( 5 + (3/8) y) + ( (2/8) y - 2)
= 5 + (3/8) y + (2/8) y - 2
Combining like terms:
= 5 + (3/8 + 2/8) y - 2
= 5 + (5/8) y - 2
Finally, simplifying:
= (5 - 2) + (5/8) y
= 3 + (5/8) y
= 3 + 5/8 y
So, the simplified form of the expression is: \boxed{3 + \dfrac{5}{8}y}
( 5 + 3/8 y) + ( 1/4 y - 2)
First, let's simplify the fractions:
( 5 + 3/8 y) + ( 1/4 y - 2)
= ( 5 + (3/8) y) + ( (1/4) y - 2)
Next, let's find the common denominator for 8 and 4, which is 8:
( 5 + (3/8) y) + ( (1/4) y - 2)
= ( 5 + (3/8) y) + ( (1/4) y * 2/2 - 2)
Simplifying further:
= ( 5 + (3/8) y) + ( (2/8) y - 2)
= 5 + (3/8) y + (2/8) y - 2
Combining like terms:
= 5 + (3/8 + 2/8) y - 2
= 5 + (5/8) y - 2
Finally, simplifying:
= (5 - 2) + (5/8) y
= 3 + (5/8) y
= 3 + 5/8 y
So, the simplified form of the expression is: \boxed{3 + \dfrac{5}{8}y}
1/8 y + 3, 1/8 y - 3, 5/8 y + 3, 5/8 y - 3. THESE R THE CHOICES CHOOSE ONE
Apologies for the confusion. After simplifying the expression ( 5 + 3/8 y) + ( 1/4 y - 2), we get:
= (5 + (5/8) y) - 2
= 5 + (5/8) y - 2
= 3 + (5/8) y
The given choices are:
1/8 y + 3,
1/8 y - 3,
5/8 y + 3,
5/8 y - 3.
The simplified expression matches the choice 3 + (5/8) y, which can be written as 5/8 y + 3.
So, the correct choice is: 5/8 y + 3.
= (5 + (5/8) y) - 2
= 5 + (5/8) y - 2
= 3 + (5/8) y
The given choices are:
1/8 y + 3,
1/8 y - 3,
5/8 y + 3,
5/8 y - 3.
The simplified expression matches the choice 3 + (5/8) y, which can be written as 5/8 y + 3.
So, the correct choice is: 5/8 y + 3.